protaTETHER - A Method for the Incorporation of Variable Linkers in Protein Fusions Reveals Impacts of Linker Flexibility in a PKAc-GFP Fusion Protein - Norris, Jessica L.; Hughes, Robert M. (My University, 2018)
Protein fusions are of fundamental importance in the study of cellular biology and the elucidation of cell signaling pathways, and the importance of linkers for the proper function of protein fusions is well documented in the literature. However, there are few convenient methods available to experimentalists for the systematic implementation of linkers in protein fusions. In this work, we describe a universal approach to the creation and insertion of focused linker libraries into protein fusions. This process, deemed protaTETHER, utilizes reiterative oligomer design, PCR-mediated linker library generation, and restriction enzyme-free cloning methods in a straightforward, three-step cloning process. We utilize a fusion between the catalytic subunit of cAMP-dependent protein kinase A (PKAc) and green fluorescent protein (GFP) for the development of the protaTETHER method, implementing small linker libraries that vary by length, sequence, and predicted secondary structural elements. We analyze the impact of linker length and sequence on the expression, activity, and subcellular localization of the PKAc-GFP fusions, and use these results to select a PKAc-GFP fusion construct with robust expression and enzymatic activity. Based upon the results of both biochemical experiments and molecular modeling, we determine that linker flexibility is more important than linker length for optimal kinase activity and expression.